Neolithic pits, late Bronze Age/early Iron Age pit alignments and Iron Age to Roman settlements at Wollaston Quarry, Northamptonshire - Atkins, Rob 1968-; Meadows, Ian (Archaeopress Publishing, 2024)
Between 1990 and 1998, MOLA (Museum of London Archaeology) undertook a series of archaeological excavations within Wollaston Quarry covering an area of 116ha. Eight excavation areas and a watching brief were undertaken revealing evidence of Neolithic pits, late Bronze Age/early Iron Age pit alignments and Iron Age to Roman settlements
At head of cover title: MOLA
Includes bibliographical references
Keywords: Vor- und Frühgeschichte; Keramik; Grube; Siedlung; Wollaston; Excavations (Archaeology) / England / Wollaston (West Midlands); Wollaston (West Midlands, England) / Antiquities; Borrow pits / England / Wollaston (West Midlands); Neolithic period / England / Wollaston (West Midlands); Northamptonshire (England) / Antiquities